Tidal disruption events: Past, present, and future. Issue 4 (28th March 2019) - Saxton, R.; Motch, C.; Komossa, S.; Lira, P.; Read, A.; Alexander, K.; Descalzo, M.; Koenig, Ö.; Freyberg, M.
Abstract : The tidal disruption of a star by a nuclear supermassive black hole was predicted in the 1970s and first confirmed by soft X‐ray flares seen from quiescent galaxies in the ROSAT all‐sky survey. We report here on the discovery of a new candidate tidal disruption event, 1RXS J075908.8 + 074835, from the ROSAT bright source catalog, which faded by a factor > 100 in 20 years. Similar events have continued to be found in XMM‐Newton and Chandra data and more recently, flares in large‐area hard X‐ray, ultraviolet (UV) and optical transient surveys have also been attributed to the same phenomenon. Each of these spectral components, sometimes complemented by radio and IR activity, have their own timescale and possibly physical mechanism. Current models and simulations revolve around trying to explain how the energy released by the fall back of stellar debris in the gravitational well of the black hole is converted into radiation in each wave band. We look at the connection between optical, UV, and X‐ray emission and illustrate a dichotomy between X‐ray and optically dominated tidal disruption event (TDE), which is currently unexplained. We look at the observations that are needed to make further breakthroughs in the field and assess the optimum follow‐up strategies needed for events discovered in future large survey missions such as extended Roentgen Survey with an Imaging Telescope Array (eROSITA), the Einstein Probe, and Large Synoptic Survey Telescope (LSST). HIgh‐energy LIght‐curve GeneraTor (HILIGT), a useful new tool for comparing fluxes and upper limits between missions, is presented.